Tren Penelitian Pengobatan Herbal untuk Penyakit Radang Usus: Analisis Bibliometrik dengan Penekanan pada Kolitis Ulseratif - Muhammad Amin Nasution; Muhammad Andry; Sry Ulina Karo-Karo; Indah Pertiwi Nasution; Meiva Amelia Lubis; Damayanti S Damayanti S (Journal of Pharmaceutical and Sciences, 2026)
Inflammatory bowel disease (IBD), particularly ulcerative colitis (UC), is a chronic gastrointestinal disorder that significantly affects quality of life. Despite advances in conventional therapy, some patients experience adverse effects, relapse, high treatment burden, or inadequate response, contributing to interest in complementary approaches, including herbal medicine. This study aims to map the development of herbal medicine research in IBD, specifically UC, by examining publication trends, key contributors, collaboration patterns, and emerging themes. This study analyzed 518 English-language journal articles indexed in Scopus from 2016 to 2025. VOSviewer (version 1.6.20) and Biblioshiny (R package version 5.0) were used to analyze source productivity, country collaboration, citation relationships, and keyword co-occurrence. Among the ten most productive sources, the Journal of Ethnopharmacology (44 articles), Frontiers in Pharmacology (24), and Phytomedicine (22) contributed 90 of 160 articles (56.3%) in the top-ten-source subset; this percentage does not represent the entire 518-document corpus. Among records with identifiable corresponding-author countries, China contributed 46.0%, followed by India (11.1%) and South Korea (8.3%). The thematic structure centered on anti-inflammatory pathways, immune modulation, DSS-induced colitis, intestinal-barrier function, gut microbiota, and emerging systems approaches such as network pharmacology and metabolomics. The journal profile and keyword network suggest that the evidence base remains predominantly preclinical and translational. Clinical validation, extract standardization, safety reporting, and multinational collaboration are therefore priorities before wider clinical adoption